Din Sosyolojisi Açısından Hac - Civil, Zafer (My University, 2003)
Hac ibadetini esas olarak dinsel bir gösteriye indirgediğimizde kesinlikle yanılırız. İslam öncesinden beri, Arap kabilelerinin Mekke'ye akın etmelerinin siyasal, ekonomik ve sosyo-kültürel bir anlamı vardı. Müminlerin hem malı hem de bedeniyle gerçekleştirdiği bir ibadet olan hac insanın bütün varlığını ilgilendirir ve bu haliyle külli bir teslimiyetin ifadesidir. Diğer yükümlülükler gibi hac da insan merkezli ve insanın ihtiyaç duyduğu hayırların tahakkukunu hedef alan bir ibadettir. Bu bakımdan onun hikmetlerini üç noktadan hareketle tespit etmek mümkündür. Bunlardan birincisi, Allah'ın insanlara bazı şeyleri yapmalarını emretmesi ve bunların yerine getirilmesi suretiyle kendilerine lütufta bulunmasıdır. İkincisi haccı gerçekleştiren insanın ona hazırlanırken, menasikini ifa ederken ve ibadetini tamamladıktan sonra kendi kabiliyetine göre elde edebildiği olumlu sonuçlar, üçüncü de bu ibadeti sadece Allah'ın rızası için yerine getiren tek tek insanların iradelerinin ve tesir alanlarının dışında haccın bütün ümmete sağladığı faydalar ve onları ulaştırdığı yüksek seviyedir. Hajj is, above all, a command for Muslims to obey. It is an act of submission that leads us to contemplate its benefits: a worldwide conference for Muslims, an occasion for Muslims to be together for the sake of God and free of all human and therefore artificial discrimination based on race, sex, color or level of education. However, it cannot be solely considered as a religious gathering of Muslims in Makka. Prior to the dawn of Islam, Hajj had also a special place among the Arab tribes with regard to its political, economic and socio-cultural effects. Hajj, one of the five pillars of Islam which Muslims perform both with their body and wealth is also related to every Muslim's very existence and represents how Muslims comply with one of God's wishes without questioning. As with other responsibilities, Hajj is also a human-centered prayer and ultimately Muslims reap the due benefits that come along with compliance with it. From this perspective, the three most important benefits of Hajj can be stated as follows: the first one is that God Almighty commands his subjects to comply with His orders and in return He bestows upon His subjects. The second one is that Muslims reap whatever gain or benefits come along with realizing the wishes of God before, during and after the completion of their Hajj. And the third one is that along with the benefits that individuals gain when they perform Hajj, the society in which they live also benefits because the spirituality of its members is increased and this, in return, increases the spiritual level of that society.
Keywords: Din; Din Sosyolojisi; Fıkıh ve fıkıh ilmi; Günümüzde yeni fıkhi meseleler; Hazer ve ibâhe; İslam Dini